OPTIMALISASI PERSEDIAAN BAHAN BAKU KERIPIK KENTANG DENGAN METODE ECONOMIC ORDER QUANTITY (STUDI KASUS DI AGRONAS GIZI FOOD) - Stefani Natalia Dinda Advenia; Maria Puri Nurani; Kukuk Yudiono (BiSTeK Pertanian, 2019)
The optimalization of raw materials supply is intended to meet the needs of raw materials for the process of the production process the future; the activity of controlling raw materials manages the implementation of necessary supply in accordance with the required amount and minimal cost, which includes the problem of purchasing raw materials, storing and maintaining materials, controlling the output of the material when materials are needed and maintaining the optimal supply amount. The raw material supply control can be analyzed using the EOQ method as one of the choices in comparing the implemented company policies. This research was conducted at Agronas Gizi Food. The analysis technique used is by comparing the results of company policy calculation and the EOQ method. The calculation of company policy includes the cost of ordering (S) with the results of Rp. 183,800 / order, supply costs (H) with a result of Rp.859 / Kg, total inventory costs (TIC) that must be spent Rp.5,689,560, the frequency of purchase 30 times, with an average purchase of 1500 kg / year while the calculation method EOQ includes economical purchases (Q*) with results of 4198 kg, frequency of purchases (F) with the result 10 times a year, total inventory costs (TIC) with the result of Rp.3,605,795, safety stock Rp.3,605,795, and ROP 234 Kg. Based on the analysis technique on raw material for potato chips in Agronas Gizi Food, it can be concluded that it is not optimal because the calculation the results of company policies are greater than the EOQ method. Keywords: Raw Materials, company policy, EOQ method